The The Experiences of Community Health Center Nurses in Providing Health Services to Obese Adolescent For Depression Prevention - Pristiana Dewi, Ari; Nur Indrawati Lipoeto; Adang Bachtiar; Yanis, Amel (AACENDIKIA: Journal of Nursing, 2025)
Depression among adolescent girls with obesity is a significant health concern that adversely impacts behavioral, emotional, and cognitive development. Addressing this condition necessitates the robust involvement of primary healthcare services; thus, understanding the lived experiences of community health center (Puskesmas) nurses in caring for this demographic is essential. This study aimed to explore the experiences of Puskesmas nurses in Pekanbaru City to identify practical barriers and inform the development of intervention strategies that are more responsive to adolescents’ psychological needs. A qualitative study utilizing an interpretive phenomenological design was conducted. Nine nurses from five Puskesmas were selected via purposive sampling. Data were gathered through 45-60 minute semi-structured in-depth interviews, transcribed verbatim, and analyzed using the Colaizzi method. The analysis revealed three core themes: (1) the utilization of adolescent health services, (2) the accessibility of healthcare delivery, and (3) specific service requirements for obese adolescent girls in depression prevention. While services were implemented through school outreach, screening, and counseling, their utilization for psychological issues remained suboptimal. Service delivery was further constrained by inconsistent participation, limited personnel, restricted service hours, and promotive-preventive programs that lacked obesity-specific targeting. Identified needs included enhanced information dissemination, strengthened cross-sectoral coordination, and the development of specialized educational media for obesity. Although adolescent health services are available at Puskesmas, they are not yet optimized for preventing depression among adolescents with obesity. This study recommends strengthening targeted programs, enhancing school-level collaboration, and developing structured educational and counseling interventions.